Criminal Recidivism: A Conceptual Analysis of Social Exclusion - B. Ahmad, Madya Abd Halim (2015)
This paper discourses the phenomena of criminal recidivism using a conceptual analysis of social exclusion. It is evidently established that, the phenomena of criminal recidivism is one of the major challenge of the contemporary criminal justice system. However, many predictors were argued by several researches as the major determinant factors of criminal recidivism in the society among the ex-prisoners. This article analyzes the criminal reoffending (recidivism) among the ex-prisoners using conceptual analysis of social exclusion of the ex-prisoners. The paper also discourses some major issues that are considered important when it comes to the analysis of social exclusion of ex-prisoners: it explains offender’s family social exclusion; absence of material and social capital of ex-prisoner; and it discourses the concept of social Ostracism as another base of social exclusion and the paper utilizes the Source-Perspective Model of Ostracism as the conceptual model of the paper. Keywords: Criminal Recidivism, Social Exclusion, Ex-Prisoner, Crime, Ostracis